2020
DOI: 10.3390/biom10030390
|View full text |Cite
|
Sign up to set email alerts
|

Altered Plasma Acylcarnitines and Amino Acids Profile in Spinocerebellar Ataxia Type 7

Abstract: Spinocerebellar ataxia type 7 (SCA7), a neurodegenerative disease characterized by cerebellar ataxia and retinal degeneration, is caused by an abnormal CAG repeat expansion in the ATXN7 gene coding region. The onset and severity of SCA7 are highly variable between patients, thus identification of sensitive biomarkers that accurately diagnose the disease and monitoring its progression are needed. With the aim of identified SCA7-specific metabolites with clinical relevance, we report for the first time, to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…While no fluid biomarkers have yet been validated for the SCAs, there are some promising candidates (Table 2 ). 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 The first candidate is the mutant protein itself in the case of the polyglutamine SCAs. In all these ataxias, the protein tends to accumulate and aggregate.…”
Section: Efforts Toward Clinical Trial Readinessmentioning
confidence: 99%
“…While no fluid biomarkers have yet been validated for the SCAs, there are some promising candidates (Table 2 ). 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 The first candidate is the mutant protein itself in the case of the polyglutamine SCAs. In all these ataxias, the protein tends to accumulate and aggregate.…”
Section: Efforts Toward Clinical Trial Readinessmentioning
confidence: 99%
“…It is observed that 8 additional pathways (depicted in green colour) have been included in the underlying network. Indicatively, the “Phospholipase D signalling pathway” , which is one of the first neighbours of the “sphingolipid metabolism” has already been mentioned in studies related to ataxia [21] , [22] , [23] , as well as pathways related to fatty acids [24] , [25] . Analysis using the 3rd methodology resulted in a larger network (depicted in Fig.…”
Section: Software Description and Methodsmentioning
confidence: 99%
“…A method which reveals modification site, but not the type of modification is amino acid analysis. By analyzing hydrolysates of native and modified protein samples, the amino acid composition can provide information about the loss of parent proteins, but also the formation of products [ 101 ]. Various protocols for the analysis of amino acids exist using derivatization with dansyl chloride or ortho -phthalaldehyde and subsequent HPLC-FLD [ 102 , 103 ] or HPLC-UV [ 104 , 105 ] or preparation of butyl esters followed by ion-pair LC-MS/MS [ 106 ].…”
Section: Analysis Of Oxidative Protein Modificationsmentioning
confidence: 99%